• sartalon@lemmy.world
      link
      fedilink
      arrow-up
      2
      ·
      2 hours ago

      X^3 = x•x•x

      X^2 = x•x

      X^1 = x

      X^0 = 1

      X^-1 = 1/x

      X^-2 = 1/(x•x)

      X^-3 = 1/(x•x•x)

      When the exponent is between -1 and 1, it becomes a root function:

      X^(1/2) = sqrt(x)

      X^(1/3) = cubic root(x)

      X^-(1/2) = 1/(sqrt(x))

      X^-(1/3) = 1/(cubic root(x))

      • JPAKx4@lemmy.blahaj.zone
        link
        fedilink
        arrow-up
        1
        ·
        12 minutes ago

        Oh I misunderstood the original comment, the teacher said it wasn’t the same, but it is the same. My understanding is that sqrt(x) = x^1/2